A Magnetohydrodynamic Model Focused on the Configuration of Magnetic Field Responsible for a Solar Penumbral Microjet - Magara, T (Astrophysical journal. Letters, 2010)
In order to understand the configuration of magnetic field producing a solar penumbral microjet that was recently discovered by Hinode, we performed a magnetohydrodynamic simulation reproducing a dynamic process of how that configuration is formed in a modeled solar penumbral region. A horizontal magnetic flux tube representing a penumbral filament is placed in a stratified atmosphere containing the background magnetic field that is directed in a relatively vertical direction. Between the flux tube and the background field there forms the intermediate region in which the magnetic field has a transitional configuration, and the simulation shows that in the intermediate region magnetic reconnection occurs to produce a clear jet-like structure as suggested by observations. The result that a continuous distribution of magnetic field in three-dimensional space gives birth to the intermediate region producing a jet presents a new view about the mechanism of a penumbral microjet, compared to a simplistic view that two field lines, one of which represents a penumbral filament and the other the background field, interact together to produce a jet. We also discuss the role of the intermediate region in protecting the structure of a penumbral filament subject to microjets.